(untitled) (Journal of Environmental Science and Natural Resources, 2015)
Banana is considered a short life commodity. Extended storage of bananas can be accomplished when ripening is not induced by a large ethylene exposure. Extension of shelf life banana would be possible by applying different promising postharvest treatments. The present study attempts to investigate the effect, of different postharvest treatments namely modified atmosphere with or without ethylene scavenging chemical (KMnO4), cooling, low temperature and hot water treatment on shelf life and quality of 3 commercially important bananas namely Sabri, Champa and Amritasagar. The two-factor experiment was laid out in completely randomized design with three replications. Sabri, Champa and Amritasagar showed significant differences in time periods to reach successive stages of ripening. Longer period was required to reach ripening stages in variety Sabri than those of Champa and Amritasagar. Postharvest treatments and varieties were found to exhibit significant variation in total soluble solids (TSS) content during storage. The variety Sabri had the highest TSS content than that of Champa and Amritasagar. An increasing trend in TSS contents was observed in all varieties at all stages of ripening. The disease severity and disease incidence wer e greatly influenced by postharvest treatments and varieties during ripening and storage. All the treatments exhibited significant effects in relation to disease incidence. Modified atmosphere packaging with ethylene scavenger (KMnO4) and storage of banana at 150C resulted in reduced disease. Disease incidence was the lowest in Sabri variety than that of Champa and Amritasagar. Different postharvest treatments and varieties showed highly significant variation on shelf life. Results showed that the shelf lives of bananas of the variety Sabri, Amritasagar and Champa were 10.81, 9.00 and 10.11 days, respectively. Sabri had the longest shelf life (16.25 days) than two other varieties. Postharvest treatments exerted significant effects to extend shelf life of bananas. The longest shelf life of 15.58 days was observed in bananas held at 150c temperature. Significant extensions of shelf life were also recorded in fruits held in plastic bags with or without KMnO4. Combinedly, the longest shelf life was found in fruits of Sabri variety at 150C. Considering the findings it may be concluded that significant variation existed due to the effects of different varieties and postharvest treatments in respect of prolongation of shelf life and other quality parameters of banana. The she lf life of banana could be extended up to 15.58 days in low storage temperature (150C) and up to 10.91 days in modified atmosphere packaging with KMnO4. The longer shelf lives of banana with the above mentioned treatments might be related to the slower changes in physico-chemical compositions. DOI: http://dx.doi.org/10.3329/jesnr.v6i2.22113 J. Environ. Sci. & Natural Resources, 6(2): 163-175 2013